Reassessing Bureaucratic Performance in Local Government through Institutional Evidence and Administrative Reali: JEL Classification: H83, H70, D73, O21, R58 - Kasmiati, Juni; Hamid, Mulyadi; Arif, Muhammad Ridwan (Journal La Bisecoman, 2025)
This research does not question the success of the State Civil Apparatus (ASN) in the Nunukan Sub-district Office in order to find out whether the case of institutional success has been attained, but rather to question the circumstances surrounding the declaring of performance. The study builds on SKP faces of 2023 and 2024 and conversations and observations in the field to reveal a troubling disjuncture between institutional measures and reality in the administrative realm. Records indicate that there is universal performance in quantity, quality, and time, but the organizational fabric paints a different picture: there is no balance in the workload, discipline is applied irregularly, motivation is presupposed but not built, and the leadership preserves the stability preserving the stability but depriving growth. In this case performance is not failing; it is done. The system of SKP, built on the vision of measuring contribution, actually turns into the engine of cloning the bureaucratic coziness, encouraging silence, and adherence to the procedures instead of results. This paper claims that performance appraisals when removed of context and criticism occupy a position where they can only be rituals that obfuscate institutional stagnation more than they can serve a corrective purpose. Rather than adding weight to the feasibility of your (collective) governance, putting border governance in an analytical standoff may question the validity of coherent assessment standards and demand the introduction of a performance paradigm that is built not on scrutiny, but structural truthfulness and societal accountability.